Crepis rhoeadifolia M. Bieb. (Compositae) in the flora of Belarus - Litvinova, Natalia A. (Experimental Biology and Biotechnology, 2022)
In 2021, the third location of Crepis rhoeadifolia M. Bieb. was identified in Belarus for the last 120 years. The article gives a phytocenotic characteristic of the habitat of C. rhoeadifolia in the Vetkovsky District of the Gomel Region, special attention is paid to the geographical distribution of the species. A map of the general range of C. rhoeadifolia has been compiled, which reflects the current distribution of the species. With the help of the MaxEnt program, the ecological and climatic niche of C. rhoeadifolia was identified, which allows us to come to the conclusion about the adventitious origin and the prospect of further distribution of the species in Belarus.